Convenient synthesis of the enantiomerically pure beta-blocker (S)-betaxolol using hydrolytic kinetic resolution - Joshi, Ramesh A.; Garud, Dinesh R.; Muthukrishnan, Murugan; Joshi, Rohini R.; Gurjar, M. K. (Tetrahedron-Asymmetry, 2005)
Enantiopure (S)-betaxolol was prepared in an extremely simple and practical way using hydrolytic kinetic resolution of a terminal epoxide by Jacobsen's catalyst. High enantiomeric purity (99% ee) has been achieved and the method is amenable to industrial scale-up. (c) 2005 Elsevier Ltd. All rights reserved.

Concise synthesis of beta-blockers (S)-metoprolol and (S)-betaxolol using hydrolytic kinetic resolution - Muthukrishnan, Murugan; Garud, Dinesh R.; Joshi, Rohini R.; Joshi, Ramesh A. (Tetrahedron, 2007)
Enantiopure (S)-metoprolol and (S)-betaxolol were prepared in an extremely simple and practical way using Jacobsen's hydrolytic kinetic resolution of terminal epoxides in isopropanol. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: beta-blockers; betaxolol; Hydrolytic kinetic resolution; metoprolol

Convenient synthesis of enantiomerically pure (R)-mexiletine using hydrolytic kinetic resolution method - Sasikumar, Murugesan; Nikalje, Milind D.; Muthukrishnan, Murugan (Tetrahedron-Asymmetry, 2009)
Enantiopure (R)-mexiletine was prepared in a simple and practical way using hydrolytic kinetic resolution method of terminal epoxide by Jacobsen catalyst. High enantiomeric purity (98% ee) was achieved and the method is well amenable to industrial scale-up. (C) 2009 Elsevier Ltd. All rights reserved.

Chiral aziridine ring opening: facile synthesis of (R)-modletine and (R)-phenoxybenzamine hydrochloride - Viswanadh, N.; Velayudham, R.; Jambu, S.; Sasikumar, M.; Muthukrishnan, Murugan (Tetrahedron Letters, 2015)
A simple and efficient synthesis of chiral drugs (R)-mexiletine 1, an anti-arrhythmic drug and (R)-phenoxybenzamine hydrochloride 2, an anti-hypertensive drug has been described via controlled reductive ring opening of chiral aziridine as a key step. The target compounds 1 and 2 were obtained in overall yields of 34% and 10.5%, respectively. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Aziridine; Mexiletine; Phenoxybenzamine